Failure analysis on the axial-connected bolts of the thin-walled cylinder under random vibration loading. (November 2019) - Gao, Daiyang; Yao, Weixing; Wu, Tao
Abstract: The axial-connected bolts of the thin-walled cylinder structure product failed under random vibration loading acted in the transverse direction. The failure modes include pull-off of the thread on the nut as well as fracture of the bolt. The fracture appearance in fractographic study shows that the failure mechanisms of the bolt connections are shear strength failure of the thread on the nut and fatigue fracture of the bolt respectively. The FEM random vibration analysis was conducted on the overall structure, and the Power Spectral Density(PSD) of the axial force on the bolt was considered as the input loading of the shear strength failure life analysis on the nut as well as the fatigue life analysis on the bolt. Finally the fatigue experiment was conducted on the simplified bolt-connected structure for verification, which showed that the failure conditions and fatigue lives of the specimens were basically the same as those of the original product. Both the results of the fracture appearance analysis and the theoretical analysis are in accordance with those of the fatigue verification experiment, which confirms the failure mechanism of the product. Highlights: The failure of the bolt connections occurred in a thin-walled cylinder structure product. The failure causes of the bolt connections were determined by fractographic analysis as well as theoretical analysis. The PSD of the axial load was obtained from FEM as the input of shear strength failure analysis and fatigue analysis. Pull-off of nut thread resulted from shear strength failure, and fracture of the bolt resulted from fatigue fracture. The results of failure analysis and failure process of the product were confirmed by the verification experiment.